EFFECTIVENESS TEST OF BIDARA LEAF EXTRACT (Ziziphus mauritiana) AS ANTIBACTERIAL AGAINST Staphylococcus aureus AND Escherichia coli - Qudsiyyah, Farida (Jurnal Biosains Pascasarjana, 2025)
Bidara leaf extract is known to have potential immunomodulatory activity, this suggests that it may provide a response to infections caused by bacteria. The results of phytochemical screening of bidara leaves taken from Klagen village, showed that there were secondary metabolite compounds in the form of flavonoids, tannins, and saponins. The inhibition zone test with the disc diffusion method using extract concentrations of 40%, 50%, 60%, 70%, 80%, 90%, and 100% as well positive control and negative control. The results showed that the diameter of the inhibition zone test was the widest of the two bacteria at Staphylococcus aureus was 10.97 ± 2.47 mm, while in Escherichia coli it was 5.26 ± 0.45 mm. The next test is the MIC test using concentrations of 100%, 50%, 25%, 12.5%, and 6.25% which is then followed by the MBC test. The results of the MIC test with the micro dilution method are known by observing changes in media turbidity after incubation. Then continued with the MBC test as confirmation of the presence of microbes after the incubation period through the pour plate method. The KHM value was obtained at a concentration of 50%, on Staphylococcus aureus bacteria with a total colony of 1.2 x 106 CFU/mL and on Eschericia coli with a total colony of 1.0 x 107 CFU/mL. The KBM value obtained on Staphylococcus aureus and Eschericia coli test bacteria is at a concentration of 100%.